THE INFLUENCE OF MEMBER PARTICIPATION AND EMPLOYEE PERFORMANCE ON THE SUCCESS OF OUR FRIENDS JAYA BONGKASA ABIANSEMAL COOPERATIVE - Putu Diah Asrida; I Gede Agus Adi Saputra (Arthaniti Studies, 2024)
This study aims to determine the effect of member participation and employee performance on the success of the Sahabat Kita Jaya cooperative Abiansemal Badung 2017-2019. The study uses a quantitative approach with a sample size of 45. Data collection techniques using questionnaires, documentation, and interviews. The analysis technique used is multiple linear regression analysis and determination test. The results of this study indicate that, (1) there is an effect of the variable participation of members on the success of the cooperative, this is based on the results of the t-test of 4.211 greater than the t-table value of 1.681 with a sig value of 0.000 <0.05. (2) there is the effect of employee performance variables on the success of cooperatives, this is based on the results of the t-test of 2.053, greater than the t-table value of 1.681 with a sig value of 0.046 <0.05. (3) there is the influence of member participation and employee performance variables on the success of the cooperative, this is based on the F-test results of 19.570, greater than the F-table value of 4.07 with a sig value of 0.000 <0.05. (4) The results of the coefficient of determination using the R Square method worth 0.482, states that there is an effect of member participation and employee performance on the success of the cooperative with a value of 48.2% while the remaining 51.8% is influenced by other factors not contained in in this research. Based on the test results above it was concluded that there was an influence between member participation and employee performance on the success of the cooperative